Nanowires of metal-organic complex by photocrystallization: a system to achieve addressable electrically bistable devices and memory elements - Rath, Arup Kumar; Dhara, Koushik; Banerjee, Pradyot; Pal, Amlan J. (Langmuir, 2008)
A new method has been achieved to form a Cu:benzoquinone derivative (DDQ) charge-transfer complex by the photoexcitation of [Cu(DDQ)2(CH3COO)2] (1) that has been synthesized by the reaction of DDQ and hydrated cupric acetate in acetonitrile. Photoexcitation of coordinated complex 1 leads to the formation of charge-transfer complex Cu2+(DDQ•−)2 (2). The charge transfer complex 2, when spun on solid substrates, forms nanowires. Sandwich structures of 2 exhibit electrical bistability associated with memory phenomenon. Read-only and random-access memory phenomena are evidenced in nanowires of 2 providing a route to attend the issues pertaining to the addressibility of organic memory devices.

Near-IR activity of hybrid solar cells: enhancement of efficiency by dissociating excitons generated in PbS nanoparticles - Guchhait, Asim; Rath, Arup Kumar; Pal, Amlan J. (Applied Physics Letters, 2010)
Photovoltaic devices based on PbSnanoparticles remained inactive in the near-IR region due to a not-so-favorable energy band-diagram that does not allow dissociation of excitons generated in PbS. In this work, with the introduction of nanostructures in the PbS-based hybrid system, we show an enhancement of photovoltaic performance in both visible and near-IR regions. The addition of increases the power conversion efficiency from 0.006% to 0.12%. With the aid of energy band-diagram, we show that excitons generated in PbS even in the near-IR range can now become dissociated to yield photocurrent in the external circuit.